The relationship of early expressed milk quantity and later full breastmilk feeding after very preterm birth: A cohort study - Ilana Levene; Frances O'Brien; Mary Fewtrell; Maria A. Quigley (Maternal and Child Nutrition)
Abstract When infants cannot directly breastfeed after birth, mothers are advised to initiate lactation through mechanical expression. Families are recommended to target an expression volume of at least 500–750 mL by Day 14 after birth, as this is considered a ‘critical window’ to establish milk supply. This is challenging for many mothers after a very preterm birth. This article explores the relationship of early milk quantity and later full breastmilk feeding as a ‘gold standard’ outcome, using statistical techniques designed for diagnostic tests. A cohort of 132 mothers of infants born at 23 + 0 to 31 + 6 weeks' gestational age submitted expressing logs on Day 4, 14 and 21 after birth and provided later feeding outcome. Using receiver operating characteristic (ROC) analysis, the following 24‐h milk quantities were identified as associated with high probability of full breastmilk at 36 weeks' post‐menstrual age (PMA): on Day 4, ≥250 g (specificity 88%; positive predictive value 88%) and on Day 21 ≥650 g (specificity 88%; positive predictive value 91%). The following values were identified as associated with low probability of full breastmilk at 36 weeks' PMA: on Day 4 <50 g (sensitivity 92%; negative predictive value 72%) and on Day 21 <250 g (sensitivity 90%; negative predictive value 70%). Participants exceeding the high thresholds had 3–4 times increased likelihood of full breastmilk, whereas those below the low thresholds had 3–5 times lower likelihood. These thresholds have potential as targets for families, to provide individualised prognostic information and to help clinicians target more intensive lactation support.